Non-parametric analysis of seed sanity and elimination and ranking indices of soybean genotypes - Vasconcelos, Edmar Soares de; Reis, Múcio Silva; Sedyiama, Tuneo; Cruz, Cosme Damião (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to assess soybean genotypes for seed sanity, with a method by which a sanity index (elimination and classification) is obtained based on non-parametric analysis. This index consisted in the elimination of genotypes with pathogen incidence above a certain value, established by the researcher, and then the classification of the noneliminated genotypes in the first step, ordering them according to the incidence of the pathogens. To verify its effectiveness, it was accomplished a simulation study and comparison of this proposed method with others, and its use in germination and sanity data of seeds from soybean lineages and cultivars of final experiments of the Soybean Breeding Program of Departmento de Fitotecnia, Universidade Federal de Viçosa, in 2002/2003 crop season. The weights of the variables and the cut limits used in the index were established considering studies related to seeds sanity and their germinations. The use of the proposed index allows the ranking of soybean genotypes, regarding to the sanitary quality of the seeds, and the elimination fromthe analyses of the genotypes that have not reached the requested minimum levels.
Keywords: Glycine max; selection index; seed physiological quality